Prevalence and characteristics of needlestick injuries among dental interns during their first-year clinical training: an observational study - Jinwei Huang; Yena Gan; He Xu; Nan Li; Na An; Zhigang Cai (BMC, 2023)
Abstract Background Dental interns are vulnerable to needlestick injuries (NSI). The objectives of this study were to examine the prevalence and characteristics of NSI exposures among dental interns during their first-year clinical training, assess risk factors, and evaluate reporting behaviours. Methods An online survey was conducted among dental interns of Class 2011-2017 at Peking University School and Hospital of Stomatology (PKUSS), China. The self-administrated questionnaire consisted of information on demographic profiles, NSI characteristics, and reporting practices. The outcomes were presented by descriptive statistics. A multivariate regression analysis was performed to assess NSI sources using a forward step-wise approach. Results A total of 407 dental interns completed the survey (response rate 91.9%, 407/443), and 23.8% sustained at least one NSI. The mean number of NSIs per intern was 0.28 during the first clinical year. More occupation exposures occurred from October to December, between 13:00-15:00. Syringe needles were the most frequent sources, followed by dental burs, suture needles, and ultrasonic chips. The risk of peer-inflicted NSIs in the department of Paediatric Dentistry was 12.1 times higher than that in Oral Surgery (OR 12.1, 95% CI: 1.4-101.4). Appropriately 64.9% NSIs occurred when chairside assistants were absent. Compared to working alone, the risk of peer-inflicted NSIs was 32.3 times higher when providing chairside assistance (OR 32.3, 95% CI: 7.2-145.4). The left-hand index finger was the most commonly injured site. About 71.4% of exposures were reported in paperwork. Conclusions Dental interns are susceptible to NSIs during their first-year clinical training. Extra attention should be paid to syringe needles, dental burs, suture needles, and ultrasonic chips. The lack of chairside assistance is hazardous regarding NSIs. The training of chairside assistance of the first-year dental interns should be enhanced. First-year dental interns are required to increase their awareness of ignored behaviors related to NSI exposures.